Collection efficiency and capacity of three samplers for acidic and basic gases - Tsai, CJ; Huang, CH; Wang, SH (My University, 2001)
This paper compares the collection efficiency and capacity of a coated porous metal disk with those of a silica gel tube and an impinger at the acid or basic aerosol concentration of two times the permissible exposure limitation (Taiwan IOSH, Institute of Occupational Safety and Health), relative humidity of 80 +/- 5%, and temperature of 30 +/- 3 degreesC in the laboratory. Using 5% sodium carbonate/glycerin coating, the collection efficiencies of the porous metal disk for nitric acid, hydrogen chloride, and hydrogen fluoride are found to be higher than those of the silica gel tube and the impinger when the sampling time is less than 3.0 h. The gas collection capacity of the porous metal disk coated with 5% sodium carbonate is calculated to be 3.9, 5.8, and >2.5 mg for nitric acid, hydrogen chloride, and hydrogen fluoride, respectively. For ammonia, the porous metal disk coated using 4% citric acid performs slightly better than the impinger, and the corresponding capacity is slightly greater than 33.6 mg.